Phase- and group-locked vector solitons in a femtosecond mode-locked Ho-laser - Chen,W; Lin,ZL; Griebner,U; Murray,RT; Mateos,X; Loiko,P; Pan,Z; Zhang,G; Petrov,V (2024)
Group-velocity locked vector solitons are observed in a mode-locked femtosecond solid-state laser at ~2 μm. Under certain conditions, stable phase-locking of the two polarizations occurs in the soliton regime: a phase- and group-locked vector soliton.